Sustainable Business Resilience: Enhancing Team Adaptability Under Strategic Uncertainty - Dedilova, Tetiana; Timchenko, Olga; Vereskun, Mykhailo; Tonkykh, Oleksii; Zelenko, Oksana (European Journal of Sustainable Development, 2025)
The article explores approaches to managing team adaptability in business in conditions of strategic uncertainty. The relevance of the topic is due to the increasing turbulence of the world economy, the impact of globalization processes, digital transformation and the need for companies to respond quickly to external challenges. The study was based on the analysis of modern adaptive management models - Agile, Lean and Holacracy, which are actively implemented in companies in the USA, the European Union and Asia. To assess the effectiveness of the application of these approaches, an analysis of real business cases and statistical indicators of the relationship between the level of team adaptability and business results was conducted: productivity, level of trust, employee involvement, company stability. The research methodology included a systematic analysis of scientific sources, a comparative analysis of management models, as well as statistical processing of data from open analytical reports and corporate research. The results obtained confirm that organizations with high team adaptability demonstrate a higher level of productivity, have lower staff turnover and better adapt to crisis situations. It has been proven that innovative management models can increase the effectiveness of team interaction, reduce stress levels among employees, and create conditions for long-term business sustainability. Further research areas include framing concrete recommendations for improving the level of adaptation of teams in a turbulent business environment. Keywords: crisis management, strategic enterprise managing, adapting team, crisis management and a digital transformation.